Analysis of Relationship between the Level of Knowledge on Stunting and Socio-demographic Characteristics among Students - Anisah Anisah; Dyah Suryani; Sitti Nur Djannah; Nurul Kodriati (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Stunting is a developmental disorder in children caused by malnutrition, repeated infections, and inadequate psychosocial simulation. The incidence of stunting will have a negative impact on the development of children during adolescence in the form of suboptimal growth. Stunting is the result of long-term nutritional deficiencies and often results in retarded mental development, poor performance and reduced intellectual capacity due to the level of knowledge and awareness of parents about the importance of meeting nutritional needs of children as the main causal factor for high stunting rate in Indonesia. Such knowledge and awareness doesnot develop automatically, and must be continuously nurtured and instilled from an early age, namely during adolescence. This study aims to determine relationship between the level of knowledge on stunting and the characteristics among the students of MA Madania of Bantul. This was a Cross Sectional Study with observational approach. Among 72 study population, the study samples were selected using Random Sampling to obtain 50 respondents. The results of the study showed that most of students had a poor level of knowledge on stunting by 80.6%, while only 19.4% of respondents who had a good level of knowledge. Furthermore, the cross-tabulation result showed that there was a relationship between the independents variable and the dependent variable with p values for gender, age and Grade of 0.04, 0.03 and 0.047, respectively, which were lower than the significant value of 0.05. There is a need for health education on nutrition for adolescents in schools in order to increase their knowledge on the incidence of stunting and nutritional problems among adolescents.